Distribution pattern of Crimean–Congo Hemorrhagic Fever in Asia and the Middle East - Aslam, Munazza; Abbas, Rao Zahid; Alsayeqh, Abdullah (Frontiers in Public Health, 2023)
Crimean–Congo Hemorrhagic Fever (CCHF) is one of the most important vector-borne diseases of zoonotic potential that can be acquired following the bite of the Hyalomma species of ticks. It is a highly prevalent disease in Asia and the Middle East. The risk factors of this disease are contact with infected tissue, blood, patient, or livestock in the acute viremic phase, infected tick bites, or the manual removal of ticks. The disease is clinically described as progressive hemorrhages, fever, and pain in musculature. Biochemical tests reveal elevated levels of creatinine phosphokinase, alanine transaminase, aspartate aminotransferase, and lactate dehydrogenase. Clotting time is prolonged in pro-thrombin tests, and pathogenesis is mostly related to the disruption of the epithelium during viral replication and indirectly by secreting cytotoxic molecules. These molecules cause endothelial activation and result in the loss of function. Supportive therapy is given through blood or plasma infusions to treat or manage the patients. According to the most advanced studies, CCHF can be treated by Ribavirin, which is an antiviral drug that shows excellent results in preventing the disease. Health-care staff are more prone to infection. The hemorrhagic phase represents a high risk for accidental exposures. This literature review presents a comprehensive overview of the viral epidemiology, zoonotic perspectives, and significant risk factors of CCHF in various Middle East and Asian countries. Furthermore, the pathophysiology and preventive strategies of CCHF have also been discussed as well as legislation and policies regarding public outreach programs, research, and development aimed at infection prevention and control that are required at a global level.